2001
DOI: 10.1016/s0008-6363(01)00369-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of parasympathetic impairment in some patients with cardiac syndrome X

Abstract: In about two thirds of the patients with SX, the pathophysiological mechanism causing the symptoms could be related to the reduced parasympathetic tone, rather than to an augmented sympathetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…Autonomic nervous system imbalance with increased adrenergic activity and impaired parasympathetic tone could explain both increased pain sensitivity and endothelial dysfunction. 34,35 More recently, Valeriani et al 36 investigated abnormalities in electric cerebral signals to pain stimuli and found decreased habituation to repetitive noxious stimuli in patients with cardiac syndrome X. In the present study, the majority of patients with syndrome X reported chest pain of moderate extent during adenosine stress.…”
Section: Karamitsos Et Alsupporting
confidence: 53%
“…Autonomic nervous system imbalance with increased adrenergic activity and impaired parasympathetic tone could explain both increased pain sensitivity and endothelial dysfunction. 34,35 More recently, Valeriani et al 36 investigated abnormalities in electric cerebral signals to pain stimuli and found decreased habituation to repetitive noxious stimuli in patients with cardiac syndrome X. In the present study, the majority of patients with syndrome X reported chest pain of moderate extent during adenosine stress.…”
Section: Karamitsos Et Alsupporting
confidence: 53%
“…Our data also do not exclude the formal possibility that a parasympathetic rather than a sympathetic dysfunction could be the cause of the autonomic imbalance. Gulli et al (29) observed reduced parasympathetic tone in two thirds of the patients with AL pain and normal coronary arteries, suggesting also an abnormal adrenergic balance. Taken together, these findings further corroborate the hypothesis that abnormal adrenergic function and response to beta-adrenergic stimulation contribute to AL pain in patients with normal coronary arteries.…”
Section: Discussionmentioning
confidence: 98%
“…It is said that the decrease in heart rate variability shows mainly in the inhibition of parasympathetic nerve function, although the impairment of the sympathetic nerve also associated with its decline. [3] And, it is known that a decline of heart rate variability shows in aging, too. [4], [5] If we can evaluate the heart rate variability properly, we can gain much information, for example, about circadian rhythm, [6], [7] cardiac disorders, [3], [6], [8] neurological disorders, [9], [10] diabetic disorders, [11]- [13]or aging.…”
Section: Discussionmentioning
confidence: 99%